The Use of the Unified Theory of Acceptance and The Use of Technology (UTAUT) to Analyze the Implementation of the Massive Open Online Course (MOOC) at the Indonesian Financial and Development Supervisory Agency - Jusuf Irianto; Isnaini Rodiyah; Khatidjah Omar (Puslatbang KDOD Lembaga Administrasi Negara, 2023)
The training and development program for the State Civil Apparatus in the public sector is very important because it is related to public performance and services. This study aims to analyze the implementation of the Massive Open Online Course (MOOC) for financial supervision training. The basic concept of this study uses an integrated Unified Theory of Acceptance and Use of Technology (UTAUT). This qualitative research was conducted at the Center for Education and Training of Auditors of the Financial and Development Supervisory Agency (Pusdiklatwas BPKP), which is responsible for training financial and development auditors. The subjects of this study were twelve informants who were selected using purposive sampling. Research data collected during the Covid-19 pandemic used electronic correspondence. The results of this study showed that training conducted using the massive open online course (MOOC) model is very effective and efficient because learning can be done flexibly and easily. Through MOOC, teachers and participants get physical facilities and troubleshooting services so that the learning process runs well without experiencing significant obstacles. This ICT-integrating training program has also positively contributed to the discipline of human resource management, especially concerning human development in organizations.